Neem leaf glycoprotein mediated immunomodulation and epigenetic regulation in Acute Myeloid Leukemia - Roshni Bibi; Shreyoshi Das; Subham Swopnil Deo; Srijita Sen; Sana Praveen; N. M. Pujitaa; R. Pradeep; Melvin George; Koustav Sarkar (Molecular Biology Reports, 2026)

Characterization of ‘Candidatus Liberibacter asiaticus’ population associated with citrus “Huanglongbing” in India by a double-locus genomic variation analysis - Ashis K. Das; Subham A. Chichghare; Prasanth Tej Kumar Jagannadham; Susheel K. Sharma; Salvinder Singh; Himanshu Pachare; Ashok Kumar; Dilip Ghosh (Physiological and Molecular Plant Pathology, 2026)

Molecular characterization and phylogenetic analysis of Fasciola gigantica from West Bengal, India using mitochondrial DNA (cox1 and nad1) as markers - Sudip Das; Subhas Chandra Mandal; Surajit Baidya; Soumitra Pandit; Ruma Jas; Subhasis Batabyal; Siddhartha Narayan Joardar; Subham Das; Nowel Chaudhury; Rupam Malakar; Ankan De; Pradyumna Chakraborty (Tropical Animal Health and Production, 2025)

Memory Element and Data Security Platforms Using Self-Sufficient Molecular Assembly Through Concentration Reliant Photo-Switching: A Latent Trait of Semicarbazone Schiff Base - Subham Chattopadhyay; Piyush Singh; Subham Das; Sujit Kumar Ghosh (Journal of Fluorescence, 2025)

Fire, anthropogenic influence, and habitat factors affect grassland persistence in the face of woody encroachment in a Terai-Duars savanna and grasslands habitat - Swapnil Bhowal; Subham Banerjee; Dhritiman Das; Robert John (Environmental Monitoring and Assessment, 2025)

Micro-level assessment of agricultural vulnerability to climate variability in Mirzapur District, Uttar Pradesh - Lucky Sharma; Shikha Singh; Priyanka Das; Priyanka Gupta; Nikhil Kumar Tiwary; Subham Oraon (Theoretical and Applied Climatology, 2025)

Effects of quercetin and derivatives on NAMPT/Sirtuin-1 metabolic pathway in neuronal cells: an approach to mitigate chemotherapy-induced cognitive impairment - Jeena John; Subham Das; Anu Kunnath; Jayesh Mudgal; Krishnadas Nandakumar (Metabolic Brain Disease, 2025)
Background: The cognitive alterations observed in individuals undergoing cancer treatments have garnered more attention recently. Chemotherapy can reduce nicotinamide adenine dinucleotide (NAD+) levels by inhibiting nicotinamide phosphoribosyl transferase (NAMPT). This reduction can make cancer cells more susceptible to oxidative damage and death and may also affect non-cancerous cells, particularly the brain cells. During chemotherapy-induced suppression, the downregulation of the NAMPT-mediated NAD+/Sirtuin 1 (SIRT1) pathway may cause dyscognition. Objective: This study aimed to assess the role of quercetin and analogues in chemobrain and the associated mechanisms. Methods: The potential of quercetin and its derivatives interaction with NAMPT and SIRT1 proteins was performed using computational studies followed by their in vitro evaluation in SH-SY5Y cells. Molecular docking and simulation studies of human SIRT1 and NAMPT proteins with quercetin and its derivatives were performed. Differentiated SH-SY5Y cell lines were treated with quercetin and selected derivatives against Methotrexate and 5-Fluorouracil (MF) toxicity, by subjecting to cytotoxicity assay, flow cytometry, and RT-PCR analysis. Results: Quercetin, Rutin, and Isoquercetin showed interactions necessary in the activation process of both proteins. Cytotoxicity and flow cytometric studies demonstrated that the phytochemicals shield the differentiated SH-SY5Y cells from MF toxicity. As determined by RT-PCR investigations, NAMPT and SIRT1 gene mRNA expression was higher in test drug-treated cells at quercetin (0.12, 0.6 µM), rutin, and isoquercetin (16, 80 µM) and lower in MF-treated cells. Conclusion: The treatment of phytochemicals alleviated CICI by targeting NAMPT and SIRT1 proteins, which could lead to the identification of effective treatment strategies for the chemobrain. Graphical abstract

Impact of EEG Reference Schemes on Event-Related Potential Outcomes: A Corollary Discharge Study Using a Talk/Listen Paradigm - Subham Samantaray; Nishant Goyal; Muralidharan Kesavan; Ganesan Venkatasubramanian; Anushree Bose; Umesh Shreekantiah; Vanteemar S. Sreeraj; Manul Das; Justin Raj; Sujeet Kumar (Brain Topography, 2025)

Identification of natural product as selective PI3Kα inhibitor against NSCLC: multi-ligand pharmacophore modeling, molecular docking, ADME, DFT, and MD simulations - Debojyoti Halder; Subham Das; R. S. Jeyaprakash (Molecular Diversity, 2024)

Spectrum of Rare and Novel Indel Mutations Responsible for β Thalassemia in Eastern India - Sajan Sinha; Atanu Kumar Dutta; Paramita Bhattacharya; Subham Bhattacharya; Mrinal Kanti Das (Indian Journal of Clinical Biochemistry, 2024)

Toxic heavy metal bioremediation potential of Pleurotus ostreatus fruit bodies grown in sugarcane bagasse supplemented substrate - Tirthankar Saha; Sagnik Das; Snigdha Sau; Debarpita Datta; Sourima Kundu; Subham Saha; Shreya Chakraborty; Bikram Dhara; Arup Kumar Mitra (Vegetos, 2024)

Ligand-based active targeting strategies for cancer theranostics - Anupriya Bandyopadhyay; Tuyelee Das; Samapika Nandy; Synudeen Sahib; Subham Preetam; Abilash Valsala Gopalakrishnan; Abhijit Dey (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Short-chain n-alkanes in benthic mats and mosses from the Larsemann Hills, East Antarctica - Subham Chatterjee; Supriyo Kumar Das; Pravat Kumar Behera; Devanita Ghosh; Arindam Chakraborty; Priyank Pravin Patel; Minoru Ikehara (Organic Geochemistry, 2023)

Grassland-woodland transitions over decadal timescales in the Terai-Duar savanna and grasslands of the Indian subcontinent - Subham Banerjee; Dhritiman Das; Hui Zhang; Robert John (Forest Ecology and Management, 2023)

Semi-analytical study on environmental dispersion of settling particles in a width-independent wetland flow - Nanda Poddar; Susmita Das; Subham Dhar; Kajal Kumar Mondal (Environmental Fluid Mechanics, 2021)

Genetic diversity and population structure of ‘Candidatus Liberibacter asiaticus’ associated with citrus Huanglongbing in India based on the prophage types - Ashis K. Das; Subham A. Chichghare; Susheel K. Sharma; J. Prasanth Tej Kumar; Salvinder Singh; Virendra K. Baranwal; Ashok Kumar; Sagar Nerkar (World Journal of Microbiology and Biotechnology, 2021)

Predicting the distribution and abundance of invasive plant species in a sub-tropical woodland-grassland ecosystem in northeastern India - Dhritiman Das; Subham Banerjee; Robert John (Plant Ecology, 2019)

Evidence of mercury trapping in biofilm-EPS and mer operon-based volatilization of inorganic mercury in a marine bacterium Bacillus cereus BW-201B - Hirak R. Dash; Subham Basu; Surajit Das (Archives of Microbiology, 2017)